Heteroaromatic alanine derivatives bearing (oligo)thiophene units : synthesis and photophysical properties - Costa, Susana P. G. (2008)
A series of new benzoxazolylalanine derivatives bearing (oligo)thiophene units at the side chain were synthesized in good yields. The photophysical characterization of these amino acids was performed by UV-vis absorption and fluorescence emission studies and revealed that some of the compounds display high fluorescent quantum yields, making them good candidates for application as fluorescent probes.